Comparative content analysis of public service announcements in USA, Russia and Kazakhstan (Herald of Journalism, 2020)
The purpose of this study is to conduct a comparative analysis of similarities and differences which are present in public service announce- ments (PSAs) of the USA, Russia and Kazakhstan. Our study examined approaches used in PSAs of each country. Findings indicate that all of the three chosen countries use similar production techniques. However, there are differences in themes, target audiences and use tactics which indicate that cultural differences play a significant role in how PSAs are produced internationally.
Keywords: public service announcements (PSAs), Kazakhstan, Rus- sia, USA, content analysis, social advertising, comparative analysis, target audiences, cultural differences.